Research on compression image in LCD to improve image quality. - Tài, Nguyễn Hữu; Hoàng - Lan, Nguyễn Thị (Journal of Computer Science and Cybernetics, 2012)
In this paper, we present a research on image compression technique in overdrive system of liquid crystal displays (LCD). The overdrive in LCD is a technique to reduce the response time of LCD, to remove drawback of motion blur caused by the slow response of liquid crystals. This problem has been studied in recent years. Image compression models in LCD are suggested in this paper. Based on research on the  models, we propose a promotion of Advanced Hybrid Image Codec (AHIC), which  has a rather simple structure, high rate of compression and rather good quality of compressed image. The promotion models is called Mean-Adaptive Image Coding (MAIC). It has high adaptive ability, so it can reduce effect of noise. Furthermore, it can  remove blocking effect which has much in AHIC. To evaluate the proposed MAIC models, we use 20 test image sequences with different features. This is the set of dedicated image, which is used for evaluation in image or video processing. Experimental results show that MAIC completely remove blocking effect error. This is a kind of error which is sensitive to human visual system, especially when watching motion image sequences. Due to these  improvements, MAIC can bring exact activity for Overdrive system and lead to enhancing image quality in LCD.